Photocatalysis by graphitic carbon nitride modified with 0D, 1D, and 2D carbon-based nanomaterials. Issue 5 (14th April 2022) - Wang, Bo-Kai; Wang, David K.; Hou, Wen-Che
Abstract : The structure–reactivity relationship of g-C3 N4 embedded with 0–2D carbon-based nanomaterials towards photocatalysis of emerging contaminants is presented. Abstract : Despite great interest in modifying graphitic carbon nitride (g-C3 N4 ) with carbon-based nanomaterials (CBNs) towards photocatalysis, no study has systematically evaluated the efficacy of 0–2D CBNs. This work examined the photocatalysis of bisphenol A and tetracycline (BPA and TC) by g-C3 N4 modified with 0D C60, 1D single-walled and multi-walled carbon nanotubes (SWCNTs and MWCNTs), and 2D graphene oxide. Notably, the relative efficacy of g-C3 N4 /CBNs in photocatalysis can be readily tuned with CBN loading contents. g-C3 N4 modified with SWCNTs (g-C3 N4 /SWCNT) usually exhibited superior photoreactivity with the only exception for 0.05% CBN loading where g-C3 N4 /MWCNT was the most photoactive. g-C3 N4 /C60 showed the least photoreactivity. The photocatalyst's surface areas, light absorption, electrical resistance, and tendency of electron–hole recombination altogether can largely explain the observed photoreactivity. Superoxide was the primary radical responsible for the photocatalysis of BPA and TC. The result indicates that both CBN types and loading amounts are influential factors in the synthesis of highly reactive g-C3 N4 modified with 0-2D CBNs, whose relative efficacy can be readily tuned with CBN loading.